Reconstructing Muslim Feminist Hermeneutics: Patriarchal Exegesis, Maqaṣidi Reading, and Substantive Gender Justice in Contemporary Islamic Thought - Amrullah; Uswatun Hasanah; Nyimas Umi Kalsum (Tanwiruna: Jurnal Pendidikan dan Sosial Keagamaan, 2026)
Gender bias in contemporary Islamic thought intensifies when historical exegesis and fiqh are treated as final theological rulings that restrict women’s experiences. This study formulates a reconstruction of Muslim feminist hermeneutics grounded in maqāṣid al-sharī‘ah and substantive justice. It applies library research by examining academic literature on Islam, gender, Muslim feminism, patriarchal exegesis, and Islamic family law. The findings show that patriarchal exegesis is shaped by androcentrism in knowledge production, atomistic readings of gender-related verses, and the absolutization of fiqh as divine will. A rereading of qiwāmah, polygamy, inheritance, and testimony affirms the need for holistic, contextual, and maqāṣid-oriented interpretation. Muslim feminist hermeneutics offers an interpretive framework grounded in Qur’anic authority while advancing reciprocity, public welfare, and substantive justice.